Curcumin regulates autophagy through SIRT3-SOD2-ROS signaling pathway to improve quadriceps femoris muscle atrophy in KOA rat model - Hua Ye; Yi Long; Jia-Ming Yang; Yan-Lin Wu; Ling-Yan Dong; Yan-Biao Zhong; Yun Luo; Mao-Yuan Wang (Scientific Reports, 2024)
Abstract Knee osteoarthritis (KOA) usually leads to quadriceps femoris atrophy, which in turn can further aggravate the progression of KOA. Curcumin (CUR) has anti-inflammatory and antioxidant effects and has been shown to be a protective agent for skeletal muscle. CUR has been shown to have a protective effect on skeletal muscle. However, there are no studies related to whether CUR improves KOA-induced quadriceps femoris muscle atrophy. We established a model of KOA in rats. Rats in the experimental group were fed CUR for 5 weeks. Changes in autophagy levels, reactive oxygen species (ROS) levels, and changes in the expression of the Sirutin3 (SIRT3)-superoxide dismutase 2 (SOD2) pathway were detected in the quadriceps femoris muscle of rats. KOA led to quadriceps femoris muscle atrophy, in which autophagy was induced and ROS levels were increased. CUR increased SIRT3 expression, decreased SOD2 acetylation and ROS levels, inhibited the over-activation of autophagy, thereby alleviating quadriceps femoris muscle atrophy and improving KOA. CUR has a protective effect against quadriceps femoris muscle atrophy, and KOA is alleviated after improvement of quadriceps femoris muscle atrophy, with the possible mechanism being the reduction of ROS-induced autophagy via the SIRT3-SOD2 pathway.